AB0563 Rituximab in patients with takayasu arteritis: a seven patients experience. (15th June 2017) - Pazzola, G; Muratore, F; Pipitone, N; Crescentini, F; Cacoub, P; Boiardi, L; Spaggiari, L; Comarmond, C; Croci, S; Saadoun, D; Salvarani, C
Abstract : Background: Takayasu arteritis (TAK) is a large vessel vasculitis involving the aorta and its major branches in patients younger than 40 years. Glucocorticoids (GCs) are the mainstay of treatment for TAK, but relapses and GC dependence are seen in more than two-thirds of patients. Increasing evidence supports a role for B cells in the pathogenesis of TAK. Circulating plasmablasts and memory B cells are increased, while naive B cells are decreased in patients with active TAK as compared with inactive and control patients [1]. These findings suggest a potential role for B cell depleting therapy in TAK. Objectives: Our aim was to assess the efficacy and safety of Rituximab (RTX) in a series of 7 patients with TAK. Methods: We conducted an open-label study on 7 TAK patients (5 followed prospectively, 2 retrospective cases) treated with RTX. All patients satisfied the American college of Rheumatology classification criteria for TAK. Six of the 7 patients had a disease refractory to high dose GCs and conventional immunosuppressive (IS) and/or biologic agents. One newly diagnosed, treatment naïve TAK patient refused GCs and received RTX alone. RTX was administered according to rheumatoid arthritis scheme (2 infusions of 1.000 mg, 15 days apart). Clinical evaluation, laboratory tests (full blood count, ESR, CRP) and imaging modalities (CTA or MRA, and PET/CT) were performed at first RTX administration and every 6 months thereafter. Disease activity was assessed using Kerr index. Radiographic disease progression was defined as new or worsening lesions at follow-up CTA or MRA. PET/CT was considered positive for active disease if two or more large vessels showed grade 2 FDG uptake or higher. Results: Seven patients (6 females) were included in the study. Mean (SD) age was 32.4 (±16.1) years. At first RTX administration, all patients had active disease according to Kerr index (≥2), and had also evidence of active disease at PET/CT. Table 1 summarizes the main results of our study. Despite RTX treatment, 4 of the 7 patients had evidence of persistent disease activity and/or radiographic disease progression during follow-up. Three out of 7 patients in whom RTX was employed as rescue therapy achieved complete remission. Conclusions: Our data do not support a role for RTX as first line biologic therapy in TAK patients, but it may have a role in some patients as second/third line biological therapy. References: Hoyer BF et al. Takayasu arteritis is characterised by disturbances of B cell homeostasis and responds to B cell depletion therapy with rituximab. Ann Rheum Dis 2012;71:75–9. doi:10.1136/ard.2011.153007. Disclosure of Interest: None declared